Comparison of trunk muscle activities in lifting and lowering tasks at various heights - Lee, Hyun (J Phys Ther Sci, 2016)
[Purpose] Biomechanical data for manual material handling are important for appropriate engineering design. The goal of this study was to investigate differences in trunk muscle activity in lifting and lowering tasks at various heights. [Subjects and Methods] Thirty healthy, young adult subjects performed 6 asymmetrical lifting and lowering tasks at various heights. Trunk muscle activity of the abdominal external oblique muscle (EO), rectus abdominis muscle (RA), and lumbar erector spinae muscles (ES) were recorded using surface electromyography (EMG). [Results] The EMG activities of the bilateral ES differed significantly among heights. The left EO activity in the ankle to knee lifting task was significantly increased compared with that of the knee to ankle lowering task. However, there were no significant differences in the right EO, bilateral ES, or RA between lifting and lowering tasks. [Conclusion] The results show that the optimal range for manual material handling was at trunk height, not only for lifting but also for lowering tasks.